Identification of Essential Oil Composition of Peel and Fruits of Citrus hystrix DC. - M.F, Safian; Ali N.A, Mohamad; , N, Yury; Ariffin Z, Zainal (Malaysian Journal of Science, 2005)
The essential oils isolated by hydrodistillation from the peel and fruits of fresh Citrus hystrix DC, were identified by GC-Kovats retention indices and GC-EI-MS. Twenty six (26) compounds have been identified from the peel and thirty seven (37) compounds have been identified from the fruit oils. The major compounds contained in peel oil were Î²-pinene (27%), limonene (24.7%) and sabinene (13.8%) while Î±-terpeneol (15.8%), Î²-pinene (15.1 %) and limonene (9.1 %) were the major compounds of fruit oil.